BK Polyomavirus Genotypes in Renal Transplant Recipients in Northern Vietnam - Hang, Dinh Thi Thu; Su, Hoang Xuan (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2018)
BK polyomavirus (BKV), a ubiquitous opportunistic infection among humans, causes BKV-associated nephropathy (BKVN) after renal transplantation. BKV strains worldwide are classified into 4 genotypes (I-IV), among which genotype I and IV are subdivided into 4 and 6 subtypes, respectively. Based on 580 bp-long VP1 sequences, this study analyzed the genotypes of 6 BKV strains from 20 specimens including plasma and urine from renal allograft recipients in Northern Vietnam. The VP1 genes of the BKV strains were analyzed by BLAST (NCBI), Bioedit, combined with MEGA7.0 software to construct and analyze the phylogenetic tree. Several mutations (8-39/ 580 nucleotides) were identified in all the 6 BKV strains compared to reference Dunlop BKV strain, among which BKV1 strain’s subtype IVc1 (isolated from the BKVN patients) had the most mutation nucleotides (39/ 580). The remaining 5 strains of BKV belonged to genotype I. The study provides a valuable fundamental molecular database contributing to monitoring as well as screening strategies and treatment options for BKV in kidney allograft recipients in Vietnam.  Keywords: BK polyomavirus, BKV-associated nephropathy (BKVN), renal transplantation, genotype. References [1] Gardner, S.D., et al., New human papovavirus (B.K.) isolated from urine after renal transplantation. Lancet, 1971. 1(7712): p. 1253-7. [2] Reploeg, M.D., G.A. Storch, and D.B. Clifford, Bk virus: a clinical review. Clin Infect Dis, 2001. 33(2): p. 191-202. [3] Randhawa, P.S., et al., Human polyoma virus-associated interstitial nephritis in the allograft kidney. Transplantation, 1999. 67(1): p. 103-9. [4] Sawinski, D. and S. Goral, BK virus infection: an update on diagnosis and treatment. Nephrol Dial Transplant, 2015. 30(2): p. 209-17. [5] Hirsch, H.H., et al., Polyomavirus-associated nephropathy in renal transplantation: critical issues of screening and management. Adv Exp Med Biol, 2006. 577: p. 160-73. [6] Bechert, C.J., et al., Monitoring of BK viral load in renal allograft recipients by real-time PCR assays. Am J Clin Pathol, 2010. 133(2): p. 242-50. [7] Takasaka, T., et al., Subtypes of BK virus prevalent in Japan and variation in their transcriptional control region. J Gen Virol, 2004. 85(Pt 10): p. 2821-7. [8] Boukoum, H., et al., Distribution of BK polyomavirus genotypes in Tunisian renal transplant recipients. J Med Virol, 2011. 83(4): p. 725-30. [9] Ledesma, J., et al., BK polyomavirus genotyping at inter- and intra-patient level in Spain. J Med Virol, 2013. 85(8): p. 1402-8. [10] Schwarz, A., et al., Viral Origin, Clinical Course, and Renal Outcomes in Patients With BK Virus Infection After Living-Donor Renal Transplantation. Transplantation, 2016. 100(4): p. 844-53. [11] An, H.P.H., et al., Ca lâm sàng nhiễm virus BK ở bệnh nhân sau ghép thận. Tạp chí Nghiên cứu Y học, 2015. 93(1): p. 142-148. [12] Hùng, T. http://benhvien198.vn/thong-bao-hai-truong-hop-nhiem-virus-bk-tren-benh-nhan-sau-ghep-than-tai-benh-vien-19-8. 2016. [13] Sharma, R., et al., BK Virus in Kidney Transplant: Current Concepts, Recent Advances, and Future Directions. Exp Clin Transplant, 2016. 14(4): p. 377-84. [14] Hayden, R.T., et al., Factors contributing to variability of quantitative viral PCR results in proficiency testing samples: a multivariate analysis. J Clin Microbiol, 2012. 50(2): p. 337-45. [15] Zhong, S., et al., Distribution patterns of BK polyomavirus (BKV) subtypes and subgroups in American, European and Asian populations suggest co-migration of BKV and the human race. J Gen Virol, 2009. 90(Pt 1): p. 144-52. [16] Matsuda, Y., Y. Qazi, and Y. Iwaki, A rapid and efficient method BK polyomavirus genotyping by high-resolution melting analysis. J Med Virol, 2011. 83(12): p. 2128-34. [17] Pastrana, D.V., et al., BK polyomavirus genotypes represent distinct serotypes with distinct entry tropism. Journal of virology, 2013. 87(18): p. 10105-10113. [18] Nishimoto, Y., et al., An Asian origin for subtype IV BK virus based on phylogenetic analysis. J Mol Evol, 2007. 65(1): p. 103-11. [19] Luo, C., et al., Genotyping schemes for polyomavirus BK, using gene-specific phylogenetic trees and single nucleotide polymorphism analysis. J Virol, 2009. 83(5): p. 2285-97. [20] Jin, L. and P.E. Gibson, Genomic Function and Variation of Human Polyomavirus BK (BKV). Rev Med Virol, 1996. 6(4): p. 201-214.